HUBUNGAN KARAKTERISTIK INDIVIDU dengan KONSEP DIRI PENDERITA TUBERKULOSIS PARU di PISKESMAS UMBULHARJO I YOGYAKARTA - Murgi Handari (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2023)
Background: Pulmonary Tuberculosis (TB) disease can affect the sufferer's self-concept. Individuals who suffer from Pulmonary TB disease often feel helpless, refuse, feel guilty, feel inferior, and withdraw from others because they are worried that the disease they are suffering from is contagious to others. A person's self-concept is not formed when a baby is born but self-concept develops in oneself and is learned through social interactions and childhood experiences. Based on Yuliana's research (2013), most of the respondents were middle-aged adults showed a relationship between self-esteem and behavior of patients with Pulmonary Tuberculosis, most of the patients were in the middle age stage (40-60 years). Sulistiyawati and Kurniawati (2012), said that pulmonary TB can interfere with the physical and psychosocial conditions of patients which affect the self-esteem of pulmonary TB patients. Pulmonary TB patients with long-term treatment will experience psychological pressure and feel worthless to their families and communities. A negative self-concept can be seen from maladaptive individual and social relationships. The components of Self-concepts are body image, self-ideal, self-esteem, self-role, and self-identity (Stuart & Sundeen, 2006). Objective: To determine the relationship between individual characteristics and self-concept of Pulmonary Tuberculosis patients at the Umbulharjo I Public Health Center Yogyakarta. Research Methods: This study used an observational analytic method with a cross sectional approach. The population in this study were all patients with Pulmonary Tuberculosis at the Umbulharjo I Health Center Yogyakarta. Data with normal distribution were analyzed using fisher's exact statistical test. Results: Most of the respondents are 15-55 years old, male, have high education (SMA – College), and have high income (Rp. 1,709,150.00). There is a significant relationship between age and self-concept (p=0.037, RR=3.50), between education and self-concept (p=0.010, RR=3.86) and between income and self-concept (p=0.000, RR= 12.14), but there is no significant relationship between gender and self-concept (p=0.343, RR=1.46) Conclusion: There is a significant relationship between age, education level and income with self concept of Puskesmas Umbulharjo I Yogyakarta